2008
DOI: 10.1371/journal.pone.0002193
|View full text |Cite
|
Sign up to set email alerts
|

Genome Sequence of Brucella abortus Vaccine Strain S19 Compared to Virulent Strains Yields Candidate Virulence Genes

Abstract: The Brucella abortus strain S19, a spontaneously attenuated strain, has been used as a vaccine strain in vaccination of cattle against brucellosis for six decades. Despite many studies, the physiological and molecular mechanisms causing the attenuation are not known. We have applied pyrosequencing technology together with conventional sequencing to rapidly and comprehensively determine the complete genome sequence of the attenuated Brucella abortus vaccine strain S19. The main goal of this study is to identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
78
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(81 citation statements)
references
References 42 publications
1
78
1
1
Order By: Relevance
“…Taken together with differences in the flanking regions, this gene locus may thus be interesting not only for diagnostic purposes ( Table 1), but also with respect to virulence and pathogenesis. So far, the most relevant difference between the virulent and chronically persisting strain B. abortus 2308 and the vaccine strain B. abortus S19 has only been described for erythritol-catabolism ( Crasta et al, 2008 andSangari et al, 2000). Most interestingly, the differences in the mglA genome region enable similar conclusions as the results of a phylogenetic 'clade' system, based on whole-genome comparisons ( Wattam et al, 2009), which describes B. ovis as an 'ancestor'…”
Section: Discussionmentioning
confidence: 94%
“…Taken together with differences in the flanking regions, this gene locus may thus be interesting not only for diagnostic purposes ( Table 1), but also with respect to virulence and pathogenesis. So far, the most relevant difference between the virulent and chronically persisting strain B. abortus 2308 and the vaccine strain B. abortus S19 has only been described for erythritol-catabolism ( Crasta et al, 2008 andSangari et al, 2000). Most interestingly, the differences in the mglA genome region enable similar conclusions as the results of a phylogenetic 'clade' system, based on whole-genome comparisons ( Wattam et al, 2009), which describes B. ovis as an 'ancestor'…”
Section: Discussionmentioning
confidence: 94%
“…These steps involve three enzymes that have not been described for any other species. Because the role of TpiA2 and RpiB in the metabolism of erythritol is now established, we propose to rename their genes eryH and eryI [the designations eryE, eryF, and eryG have already been proposed for the erythritol transport system of B. abortus (21)]. The gene encoding the putative regulatory protein DeoR, which precedes tpiA2 on the chromosome, has been designated eryR by Geddes and colleagues (13).…”
Section: Discussionmentioning
confidence: 99%
“…Despite genetic differences of B. abortus S19 from wild-type strains commonly isolated in nature (Crasta et al 2008), S19 has been shown to cause disease in mice that is similar to that in large animals, especially in the reproductive tract, supporting its utility as an effective model (Enright et al 1990;Kim et al 2005). The selection of T. musculi, the patho-adapted species of trypanosome for mice, was based on the benign nature which appeared similar to reports of T. cervi in elk (Albright and Albright 1981).…”
Section: Discussionmentioning
confidence: 99%